Effect of Soil Solarization Using Ldpemulch on Moisture Conservation and Soil Temperature Variation - Anu Varghese (Department of Land and Water Resources and Conservation Engineering, Kelappaji College of Agricultural Engineering and Technology, 1997)
Soil solarization is based on mulching the soil surface with transparent polyethylene sheets which capture the solar radiation and thus heat the soil to a level lethal for various pests. Solarization is useful in the control of weeds and also helps in moisture conservation. To some extent this can satisfy the demand of water for pre sowing irrigation during the summer months by conserving the moisture in the soil. In the experiment two types of polyethylene sheets (0.10 mm and 0.05 mm) were used and three durations of solarization, i.e., 30 days, 40 days and 50 days were tried. A crop (bhindi) was sown in the area after the solarization period to know the effect of solarization on its performance. The average maximum soil temperature at 5 cm depth obtained in the non-solarized plots was 49.5°C only, but in solarized plots it went upto 56.5°C. The magnitude of rise in soil temperature of solarized treatments was higher due to 0.05 TP than 0.10 TP. The intensity of solar radiation reaching the soil surface was significantly higher in the non-solarized plots than in the solarized plots. There was significant increase in the moisture content values in the solarized plots compared to the non solarized plots at 5, 10 and 15 cm depth below the soil surface. The moisture content values in 0.05 TP solarized plots were slightly higher than